Faculty Perspectives on Professional Development in Nepalese Higher Education - Giri, Surendra; Devkota, Kamal Raj; Thasineku, Om Chandra; Khanal, Dipak; Kshetree, Arun Kumar (Interdisciplinary Issues in Education, 2024)
This paper is a part of a comprehensive research conducted by CERID, TU, on professional development practices of the faculty members in higher education in Nepal. Delving into different professional development practices including research and publications, this paper unpacks the aspirations and challenges that the faculty members experienced in relation to their professional engagements. Quantitative information derived from survey and qualitative information derived from a series of FGDs, interviews and case study were analyzed to unpack the existing professional practices and aspirations that they university faculty members have had regarding their professional development. More importantly, this paper unfolds the challenges that the faculty members confronted with while engaging in different professional development practices involving research and publications, grants and facilities that they receive in this regard, professional development spaces that the concerned universities and campuses have created for them. This paper suggests that the policy makers and the concerned authorities of the universities and the affiliated campuses should stress the continuous professional development practices of teacher faculty members in their policies and programmes. This strengthens the overall quality of the teacher performance and quality of higher education in Nepal.